Stelsels substitutie (reeks 2)

Hoofdmenu Eentje per keer 

Substitutie

  1. \(\left\{\begin{matrix}2x-3y=\frac{-52}{3}\\-3x=y+-7\end{matrix}\right.\)
  2. \(\left\{\begin{matrix}-2x+5y=\frac{-76}{9}\\3x=y+\frac{112}{15}\end{matrix}\right.\)
  3. \(\left\{\begin{matrix}-3x-y=\frac{89}{35}\\-2x=4y+\frac{76}{35}\end{matrix}\right.\)
  4. \(\left\{\begin{matrix}-4x-6y=31\\x=y+\frac{-11}{4}\end{matrix}\right.\)
  5. \(\left\{\begin{matrix}-4y=\frac{-19}{70}-3x\\x-4y=\frac{247}{70}\end{matrix}\right.\)
  6. \(\left\{\begin{matrix}6y=\frac{-122}{15}+x\\-2x+3y=\frac{-407}{30}\end{matrix}\right.\)
  7. \(\left\{\begin{matrix}-5x+y=\frac{-11}{6}\\-3x=3y+\frac{-13}{2}\end{matrix}\right.\)
  8. \(\left\{\begin{matrix}-5y=\frac{299}{34}+6x\\-x+5y=\frac{473}{68}\end{matrix}\right.\)
  9. \(\left\{\begin{matrix}-x-3y=\frac{-60}{7}\\3x-4y=\frac{-95}{14}\end{matrix}\right.\)
  10. \(\left\{\begin{matrix}-5x-6y=\frac{477}{85}\\-5x=-y+\frac{358}{85}\end{matrix}\right.\)
  11. \(\left\{\begin{matrix}3x+3y=\frac{1080}{77}\\6x=y+\frac{620}{77}\end{matrix}\right.\)
  12. \(\left\{\begin{matrix}4x+3y=\frac{-3}{20}\\x=-3y+\frac{-57}{20}\end{matrix}\right.\)

Substitutie

Verbetersleutel

  1. \(\left\{\begin{matrix}2x-3y=\frac{-52}{3}\\-3x=y+-7\end{matrix}\right.\qquad V=\{(\frac{1}{3},6)\}\)
  2. \(\left\{\begin{matrix}-2x+5y=\frac{-76}{9}\\3x=y+\frac{112}{15}\end{matrix}\right.\qquad V=\{(\frac{20}{9},\frac{-4}{5})\}\)
  3. \(\left\{\begin{matrix}-3x-y=\frac{89}{35}\\-2x=4y+\frac{76}{35}\end{matrix}\right.\qquad V=\{(\frac{-4}{5},\frac{-1}{7})\}\)
  4. \(\left\{\begin{matrix}-4x-6y=31\\x=y+\frac{-11}{4}\end{matrix}\right.\qquad V=\{(\frac{-19}{4},-2)\}\)
  5. \(\left\{\begin{matrix}-4y=\frac{-19}{70}-3x\\x-4y=\frac{247}{70}\end{matrix}\right.\qquad V=\{(\frac{-19}{10},\frac{-19}{14})\}\)
  6. \(\left\{\begin{matrix}6y=\frac{-122}{15}+x\\-2x+3y=\frac{-407}{30}\end{matrix}\right.\qquad V=\{(\frac{19}{3},\frac{-3}{10})\}\)
  7. \(\left\{\begin{matrix}-5x+y=\frac{-11}{6}\\-3x=3y+\frac{-13}{2}\end{matrix}\right.\qquad V=\{(\frac{2}{3},\frac{3}{2})\}\)
  8. \(\left\{\begin{matrix}-5y=\frac{299}{34}+6x\\-x+5y=\frac{473}{68}\end{matrix}\right.\qquad V=\{(\frac{-9}{4},\frac{16}{17})\}\)
  9. \(\left\{\begin{matrix}-x-3y=\frac{-60}{7}\\3x-4y=\frac{-95}{14}\end{matrix}\right.\qquad V=\{(\frac{15}{14},\frac{5}{2})\}\)
  10. \(\left\{\begin{matrix}-5x-6y=\frac{477}{85}\\-5x=-y+\frac{358}{85}\end{matrix}\right.\qquad V=\{(\frac{-15}{17},\frac{-1}{5})\}\)
  11. \(\left\{\begin{matrix}3x+3y=\frac{1080}{77}\\6x=y+\frac{620}{77}\end{matrix}\right.\qquad V=\{(\frac{20}{11},\frac{20}{7})\}\)
  12. \(\left\{\begin{matrix}4x+3y=\frac{-3}{20}\\x=-3y+\frac{-57}{20}\end{matrix}\right.\qquad V=\{(\frac{9}{10},\frac{-5}{4})\}\)
Oefeningengenerator vanhoeckes.be/wiskunde 2021-12-02 00:50:58